Identifying Clinical Improvement in Consolidation Single-Arm Phase 2 Trials in Patients With Ovarian Cancer in Second or Greater Clinical Remission. Issue 1 (1st January 2012) - Iasonos, Alexia; Sabbatini, Paul; Spriggs, David R.; Aghajanian, Carol A.; O'Cearbhaill, Roisin E.; Hensley, Martee L.; Thaler, Howard T.
Abstract : Objective: Estimates of progression-free survival (PFS) from single-arm phase 2 consolidation/maintenance trials for recurrent ovarian cancer are usually interpreted in the context of historical controls. We illustrate how the duration of second-line therapy (SLT), the time on the investigational therapy (IT), and patient enrollment plan can affect efficacy measures from maintenance trials and might result in underpowered studies. Methods: Efficacy data from 3 published single-arm consolidation therapies in second remission in ovarian cancer were used for illustration. The studies were designed to show an increase in estimated median PFS from 9 to 13.5 months. We partitioned PFS as the sum of the duration of SLT, treatment-free interval, and duration of IT. We calculated the statistical power when IT is given concurrently with SLT or after SLT by varying the start of IT. We compared the sample sizes required when PFS includes the time on SLT versus PFS that starts after SLT at initiation of IT. Results: Required sample sizes varied with duration of SLT. If IT starts with initiation of SLT, only 34 patients are needed to provide 80% power to detect a 33% hazard reduction. In contrast, 104 patients are required for a single-arm study for 80% power, if IT begins 7.5 months after SLT initiation. Conclusions: Designs of nonrandomized consolidation trials that aim to prolong PFS must consider the effect of the duration of SLT on the end point definition and on required sample size. If IT is given concurrently with SLT, and after SLT, then SLT duration must be restricted per protocol eligibility, so that a comparison with historical data from other single-arm phase 2 studies is unbiased. If IT is given after SLT, the duration of SLT should be taken into account in the design stage because it will affect statistical power and sample size.